The Portrayal of Sutter Keely’s Defense Mechanism During Adolesence In The Spectacular Now - Natasha Ivana; Arido Laksono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
This thesis is written to analyze the main character, Sutter Keely, in The Spectacular Now by Tim Tharp, who struggles his adolescence without proper parental guidance. He is also dealing with failed romantic relationships that influence in how he grows as an adolescent. In this novel, he uses several defense mechanisms on daily basis to deal with issues and difficulties in his life. This thesis aims to identify the triggers, the kinds, and the effects of his defense mechanisms. This thesis uses Freudian psychoanalysis theory and its branch, defense mechanism, as the main theories. Library research and exponential approach are used to help the writer to get the desirable results. The result of this thesis reveals that the main triggers of his defense mechanisms are his family and his failed romantic relationships. The defense mechanisms he uses are rationalization, displacement, suppression, denial, altruism, and distortion. The effects of his defense mechanisms bring more negative results to his life.Keywords: adolescence; defense mechanisms; Freudian Psychoanalysis.